Effects of Tamsulosin on Premature Ejaculation in Men with Benign Prostatic Hyperplasia - Choi, Jae Hwi; Hwa, Jung Seog; Kam, Sung Chul; Jeh, Seong Uk; Hyun, Jae Seog (The world journal of men's health, 2014)
Previous studies have revealed that tamsulosin is effective in improving lower urinary tract symptoms (LUTS) and erectile functioning but has some inhibitory effects on ejaculation, including decreased ejaculatory volume. However, these inhibitory effects on ejaculation can be beneficial to patients with premature ejaculation (PE). Therefore, this study was conducted to understand the effect of tamsulosin on PE in men with benign prostatic hyperplasia. Twenty-nine patients who visited with LUTS were categorized into 2 groups of LUTS-only patients (n=12) and LUTS combined with PE (LUTS+PE) patients (n=17), and 0.4 mg of tamsulosin was administered to the patients of both groups for 12 weeks. Comparative analyses of before and after the treatment were conducted for calculating the International Prostate Symptom Score (IPSS), International Index of Erectile Function-5 (IIEF-5), intravaginal ejaculatory latency time (IELT), premature ejaculation diagnostic tool (PEDT), and premature ejaculation profile (PEP). The patients with an IPSS score of 8 or higher were determined as LUTS patients, and the patients with IELT of less than 2 minutess and a PEDT score of 9 or higher were determined as PE patients. After treatment, the IPSS score significantly decreased in both groups. There was no statistically significant change in the PEDT for the LUTS group, but there was a significant decrease in PEDT (p=0.012; from 12.1±3.31 to 8.4±4.49) in the LUTS+PE group. Tamsulosin not only has a treatment effect for LUTS but also improves the PE of LUTS+PE patients. Therefore, further studies are needed to confirm the effects of tamsulosin on PE.